Resolvin D2 induces anti-microbial mechanisms in a model of infectious peritonitis and secondary lung infection - Sundarasivarao, Prem Y. Kadiyam; Walker, Jean M.; Rodriguez, Ana; Spur, Bernd W.; Yin, Kingsley (Frontiers in Immunology, 2022)
In severe bacterial infections, there is a pro-inflammatory response to promote bacterial clearance but this response can cause tissue injury. Later, the immune system becomes dysregulated and the host is unable to clear a secondary or a pre-existing infection. Specialized Pro-resolving Mediators (SPMs) such as resolvin D2 (RvD2) have been shown to be beneficial for inflammation/infection resolution in animal models of sepsis but in vivo mechanisms by which RvD2 may promote bacterial clearance and/or attenuate deleterious effects of a secondary infection have not been fully established. In this study, we used the 2-hit model of cecal ligation and puncture (CLP) induced infectious peritonitis and secondary lung infection with Pseudomonas aeruginosa to find possible antimicrobial and immunomodulatory mechanisms of RvD2. We show that RvD2 given as late as 48h after CLP surgery reduced blood bacterial load without altering plasma cytokines compared to mice given saline vehicle. RvD2 increased splenic neutrophil accumulation as well as average reactive oxygen species (ROS) production. There was also an increase in an immature leukocyte population the myeloid derived suppressor cells (MDSCs) in the spleen of RvD2 treated mice. RvD2 reduced lung lavage bacterial load 24h after P. aeruginosa administration and significantly decreased lung lavage levels of IL-23, a cytokine essential in the Th-17 inflammatory response. In addition, we show that RvD2 increased the number of non-inflammatory alveolar macrophages after P. aeruginosa administration compared to saline treated mice. The study uncovered an antimicrobial mechanism of RvD2 where RvD2 increases mature neutrophil and MDSC accumulation into the spleen to promote blood bacterial clearance. The study showed that in this 2-hit model, RvD2 promotes lung bacterial clearance, increased non-inflammatory alveolar macrophage number and inhibits an adaptive immune pathway providing evidence of its resolution mechanism in secondary pulmonary infection.